Perspektif Konsumen pada Kepuasan Belanja pada Konsumen Gen Z - Puja Hermawati (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the influence of sustainable marketing strategies on Generation Z consumers' shopping satisfaction and to evaluate the role of consumer perspectives on sustainability values as a mediating variable. The background of this research is based on the shifting consumption behavior of Generation Z, which tends to be responsive to ethical, transparent, and environmentally oriented business practices. This study employs a quantitative explanatory approach with data collected through a Likert-scale questionnaire. The sample consists of 385 respondents selected using purposive sampling. Data analysis was conducted using multiple linear regression and path analysis with the SmartPLS software. The results indicate that sustainable marketing has a significant effect on shopping satisfaction, both directly and through the mediation of consumers’ sustainability perspectives. The findings highlight the importance of integrating sustainability values into corporate marketing strategies to enhance satisfaction and foster loyalty among young consumers